A GRI-BASED ESG DISCLOSURE DATASET FOR PALM OIL, PULP AND PAPER, AND FORESTRY COMPANIES IN INDONESIA - Tegar; Disman; Heny Hendrayati; Puspo Dewi Dirgantari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article presents an original Environmental, Social, and Governance (ESG) disclosure dataset constructed through systematic dual-coder content analysis for Indonesian forest-utilizing companies listed on the Indonesia Stock Exchange (IDX). The dataset encompasses 71 company-year observations from 41 unique companies across fiscal years 2023 and 2024, covering three sectors: palm oil (21 companies, 37 observations), pulp and paper (11 companies, 21 observations), and forestry and wood products (9 companies, 13 observations). ESG disclosure was assessed using 144 indicators derived from the Global Reporting Initiative (GRI) Standards, comprising 72 Governance, 32 Environmental, and 40 Social items. Each indicator was scored using a binary approach (1 = disclosed, 0 = not disclosed), with inter-coder reliability yielding Cohen's kappa coefficients of 0.85 to 0.91. This dataset addresses a critical gap in ESG disclosure research for Indonesia's forest-utilizing sector, which faces increasing international scrutiny under the European Union Deforestation Regulation (EUDR). The data can be reused for analyzing disclosure determinants, conducting subsector comparisons, evaluating the effectiveness of sustainability certification schemes, and benchmarking corporate transparency against regulatory requirements. The full dataset is publicly deposited at Mendeley Data (DOI: 10.17632/hnsb3h9353.2) under a CC BY 4.0 license.